Expression of Osteoprotegrin and Osteoclast Level in Chronic Apical Periodontitis Induced with East Java Propolis Extract - Yuanita, Tamara; Zubaidah, Nanik; Kunarti, Sri (Iranian Endodontic Journal, 2019)
Introduction: The objective of this animal study was to promote East Java propolis as a potential natural intracanal medicament for periapical chronic apical periodontitis bone resorption through evaluating the expression of osteoprotegrin (OPG) and osteoclast level. Methods and Materials: Propolis extract was produced using a maceration procedure. Thirty Wistar rats were divided into three groups. In group I, the control group, the first upper right molar constituted a healthy tooth. In group II, containing rodents with experimentally chronic apical periodontitis, infection with Enterococcus faecalis ATCC29212 106 CFU was performed. In group III, the treatment group, after being injected with E faecalis, 10 µL propolis was applied. It required 21 days to induce post-pulp chronic apical periodontitis infection. The rats were euthanised for immunohistochemical examination in order to measure the expression of OPG and to count histologically the number of osteoclast. Result: The expression of OPG and osteoclast constituted 17.5±1.58 and 6.4±0.96 in group I, 10±2 and 16.2±1.31 in group II and 17±1.69 and 7.5±1.08 in group III. Group I presented the highest level of OPG expression but the lowest level of osteoclast expression. There were significant differences between groups II and III and group I regarding OPG and osteoclast expression (P<0.05). Conclusion: East Java Propolis was a potential intracanal medicament promoting an increase in osteoprotegerin expression and a decrease in the number of osteoclasts thereby inhibiting osteoclastogenesis. Keywords: Chronic Apical Periodontitis; East Java Propolis; Intracanal Medicament